5. EVALUATION OF COMPLIANCE WITH VENTILATOR-ASSOCIATED PNEUMONIA PREVENTIVE BUNDLES AT THE CENTER FOR ANESTHESIA AND SURGICAL INTENSIVE CARE IN BACH MAI HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Background: Ventilator-associated pneumonia (VAP) is a common complication in mechanically ventilated patients in intensive care units. A VAP preventive bundle developed by the National Center for Global Health and Medicine of the Ministry of Health, Japan consisting of 10 measures has been transferred and applied at Bach Mai Hospital. The study was conducted to evaluate the level of compliance with the preventive bundle and the incidence of VAP.Research methods: A prospective observational study was conducted at Center for Anesthesia and Surgical Intensive Care, Bach Mai Hospital from December 2023 to June 2024, to monitor compliance with VAP preventive bundle. The study included all patients ≥ 18 years old, mechanically ventilated after surgery, and without previous pneumonia, and excluded those who were mechanically ventilated for less than 48 hours. The incidences of compliance with measures and prevalence of VAP were monitored and recorded.Results: There were 337 patients who met the study criteria. The incidence of VAP in the patient group was 25.2% (frequency 36.5 cases/1000 ventilator days). The overall compliance rate of the VAP preventive bundle was 66.5%. Compliance rates > 80% were achieved for hand hygiene, head elevation 30-45 degrees, oral hygiene, breathing circuit management and cuff pressure management, and gastric ulcer and deep vein thrombosis prevention. The compliance rates for sedation management, use of hypoplastic suction, daily spontaneous breathing trial and weaning, and early bed leaving were below 50%.Conclusion: The overall compliance rate of the VAP preventive bundle was 66.5%. The incidence rate of VAP in the study was 25.2%.
Keywords: Ventilator-associated pneumonia; preventive bundle; compliance; resuscitation unit